Resource selection modeling reveals potential conflicts involving reintroduced lions in Tembe Elephant Park, South Africa - Millspaugh, J. J.; Rittenhouse, C. D.; Montgomery, R. A.; Matthews, W. S.; Slotow, R. (Journal of zoology (1987), 2015)
Ecotourism has motivated efforts to reintroduce lions (Panthera leo) to landscapes where they were not previously common. In 2002, four lions were reintroduced into the fenced Tembe Elephant Park, South Africa to improve ecotourism opportunities, but lions potentially compete for habitat with humans and endemic herbivores of conservation concern. We developed a population‐level resource selection function to map the relative probability of lion occurrence throughout Tembe Elephant Park to predict the spatial distribution of potential conflicts. In winter, high relative probability of lion occurrence spatially overlapped with Muzi reedbeds/hygrophilous grassland habitat, which is where humans gather natural resources. Comparatively, we found no spatial overlap with sand forest habitat used by endemic herbivores. The results were opposite in summer, with lion occurrence overlapping sand forest habitat and no predicted overlap with Muzi reedbeds/hygrophilous grassland habitat. During spring and autumn, the highest relative probability of lion occurrence spatially overlapped both Muzi reedbeds/hygrophilous grassland and sand forest habitats. These results show that lions might compete with humans in winter, spring and autumn and with endemic herbivores in all seasons but winter. Despite the success of reserve fencing in limiting human–lion conflicts, we show that communities that reintroduce carnivores continue to balance relative reward, associated with ecotourism, and risks to human safety and species of conservation concern. We discuss the importance of dynamic management practices that ensure temporal segregation between humans and lions within specific habitat types.